2020
DOI: 10.3389/fimmu.2020.571049
|View full text |Cite
|
Sign up to set email alerts
|

Infection With Clostridioides difficile Attenuated Collagen-Induced Arthritis in Mice and Involved Mesenteric Treg and Th2 Polarization

Abstract: Objectives: Rheumatoid arthritis is an autoimmune disease with multifactorial etiopathogenesis. Among the environmental factors, mucosal infections and the inducing pathobionts are gaining increasing attention. We here set out to explore the gut-joint-axis and the impact of Clostridioides difficile infection on subsequent arthritis. Methods: We combined C. difficile infection in DBA/1J × B10.Q F1 mice with collagen induced arthritis (CIA). Mice were infected via oral gavage and infection was monitored by weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, for the genus Clostridium , Schmidt et al. found that infection with Clostridioides (Clostridium) difficile VPI 10463 induced intestinal inflammation and thus reduced the incidence of collagen induced arthritis (CIA) in mice ( 46 ). Moreover, we identified several other restored species and functions that are not consistent with previous studies, possibly due to treatment differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the genus Clostridium , Schmidt et al. found that infection with Clostridioides (Clostridium) difficile VPI 10463 induced intestinal inflammation and thus reduced the incidence of collagen induced arthritis (CIA) in mice ( 46 ). Moreover, we identified several other restored species and functions that are not consistent with previous studies, possibly due to treatment differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our murine CDI model is broadly used due to the ability to mimic severe diarrhea presented by humans and was performed as previously described (31)(32)(33)(34)(35). C57BL/6 mice (n=6 for each group) received an antibiotic treatment (0.035 mg per mL gentamicin, 850 U per mL colistin, 0.215 mg per mL metronidazole, and 0.045 mg per mL vancomycin) in the drinking water for 3 days.…”
Section: Difficile Infection Modelmentioning
confidence: 99%
“…Our murine CDI model was established as previously described (Chen X. et al, 2008;Moore et al, 2015;Shin et al, 2017;Broecker et al, 2019;Schmidt et al, 2020). This model is broadly used due to the ability to mimic clinical symptoms, such as severe diarrhea, presented by humans with CDI (Chen X. et al, 2008;Moore et al, 2015;Shin et al, 2017;Broecker et al, 2019;Schmidt et al, 2020). C57BL/6 mice (n = 5 for each group) received an antibiotic treatment in the drinking water for 3 days.…”
Section: Difficile Infection Modelmentioning
confidence: 99%